Excessive toxicity of cabozantinib in a phase II study in patients with recurrent and/or metastatic salivary gland cancer. (January 2022) - van Boxtel, Wim; Uijen, Maike J.M.; Krens, Stefanie D.; Dijkema, Tim; Willems, Stefan M.; Jonker, Marianne A.; Pegge, Sjoert A.H.; van Engen-van Grunsven, Adriana C.H.; van Herpen, Carla M.L.
Abstract: Aim: Because the tyrosine kinases c-MET and vascular endothelial growth factor receptors (VEGFR) are often overexpressed in salivary gland cancer (SGC), this study evaluated the efficacy and safety of cabozantinib in patients with recurrent/metastatic (R/M) SGC. Patients and methods: A single-centre phase II study was conducted. Patients with immunohistochemical c-MET-positive R/M SGC were included in three cohorts: adenoid cystic carcinoma (ACC); salivary duct carcinoma (SDC) and other miscellaneous SGCs. No prior systemic treatments were required. Patients started cabozantinib 60 mg once daily. The primary outcome was the objective response rate (ORR). Secondary outcomes included survival, safety and quality of life. Per Simon-two-stage design, depending on efficacy, a maximum of 43 patients would be included. Results: In total, 25 patients were included until premature closure owing to severe toxicity. Six patients (24%) had grade 3–5 wound complications, occurring at a median of 7.1 months on cabozantinib treatment (range 2.1–12.6). Remarkably, four of these six patients developed this complication in the area prior exposed to high-dose radiotherapy. Other grade ≥3 adverse events in >1 patient were hypertension (20%), diarrhoea (8%) and dehydration (8%). Twenty-one patients were evaluable for response; 1/15 ACC (ORR: 7%); 1/4 SDC and 0/2 patients with other miscellaneous SGC responded. Median progression-free survival was 9.4 months (95% confidence interval [CI] 7.4–11.4 months), 7.2 months (95%CI 0.0–15.1) and 6.9 months (95%CI 0.0–15.1), respectively. Conclusion: This study showed too many severe cabozantinib-associated wound complications in patients with SGC, especially in prior irradiated areas. Therefore, the study closed prematurely. The efficacy in the limited number of evaluable patients was low to moderate. Trial registration: This trial was registered on ClinicalTrials.gov: NCT03729297. Highlights: Phase II study of cabozantinib in patients with salivary gland cancer. Study closed prematurely owing to severe wound complications. Wound complications occurred especially in prior irradiated areas. The efficacy of cabozantinib was low to moderate in this study. Caution with cabozantinib is advised in patients with prior high-dose radiotherapy.